Macrophage receptors implicated in the "adaptive" form of innate immunity. - Bowdish, D; Loffredo, MS; Mukhopadhyay, S; Mantovani, A; Gordon, S (2007)
The adaptive component of innate immunity occurs during the course of infection when antigen presenting cells alter expression of soluble or surface associated pattern recognition receptors. This results in increased recognition of a broad spectrum of pathogens, enhancement of effector functions and altered regulation of the inflammatory response.